Pediatric heart transplantation - indication and preoperative assessment - Iolanda Muntean; Asmaa Carla Barmou; Daniela Toma (Amaltea Medical Publishing House, 2020)
Pediatric heart transplantation is now considered a standard therapeutic care for infants and children with end stage heart disease. The indication for heart transplantation depends on the etiology of heart failure, and therefore is related to the age of the children: congenital heart defects predominate in infants and cardiomyopathies in older children. Because of the evolvement in surgical strategy of the congenital heart defects, the indication for heart transplantation is in continuous upgrading. The waiting list is stratified according to the patient status. This review focuses on the indications for pediatric heart transplantation. Also, because of the need of a rigorous assessment of the potential recipients, we present a check-list for the pretransplantation assessment of the receptor.